2018
DOI: 10.1016/j.stemcr.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Isogenic FUS-eGFP iPSC Reporter Lines Enable Quantification of FUS Stress Granule Pathology that Is Rescued by Drugs Inducing Autophagy

Abstract: SummaryPerturbations in stress granule (SG) dynamics may be at the core of amyotrophic lateral sclerosis (ALS). Since SGs are membraneless compartments, modeling their dynamics in human motor neurons has been challenging, thus hindering the identification of effective therapeutics. Here, we report the generation of isogenic induced pluripotent stem cells carrying wild-type and P525L FUS-eGFP. We demonstrate that FUS-eGFP is recruited into SGs and that P525L profoundly alters their dynamics. With a screening ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 27 publications
(34 reference statements)
6
88
0
Order By: Relevance
“…In all cases, TDP-43 de-mixes initially into liquid droplets (with rapid molecular exchange with soluble TDP-43 molecules) but converts to rounded gel/solid-like structures with arsenite exposure. The interaction of TDP-43 (Afroz et al, 2017;Becker et al, 2017;Khalfallah et al, 2018;Li et al, 2013;Ramaswami et al, 2013) or FUS Hofweber et al, 2018;Li et al, 2013;Marrone et al, 2018;Zhang et al, 2018) with stress granules has repeatedly been proposed to be a means to enhance their subsequent aggregation. In contrast, we have found that cytoplasmic LLPS of TDP-43 can be independent of components of stress granules and stress granule assembly despite initial recruitment of a small proportion of TDP-43 into stress granules induced with a high dose of sodium arsenite.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, TDP-43 de-mixes initially into liquid droplets (with rapid molecular exchange with soluble TDP-43 molecules) but converts to rounded gel/solid-like structures with arsenite exposure. The interaction of TDP-43 (Afroz et al, 2017;Becker et al, 2017;Khalfallah et al, 2018;Li et al, 2013;Ramaswami et al, 2013) or FUS Hofweber et al, 2018;Li et al, 2013;Marrone et al, 2018;Zhang et al, 2018) with stress granules has repeatedly been proposed to be a means to enhance their subsequent aggregation. In contrast, we have found that cytoplasmic LLPS of TDP-43 can be independent of components of stress granules and stress granule assembly despite initial recruitment of a small proportion of TDP-43 into stress granules induced with a high dose of sodium arsenite.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study provides an additional proof of concept that modulating autophagy may be of therapeutic interest in ALS/FTD. Indeed, previous studies have shown that stimulating autophagy is beneficial in SOD1, FUS, and TDP‐43 cell or animal models of ALS (Hetz et al , ; Crippa et al , ; Wang et al , ; Castillo et al , ; Barmada et al , ; Perera et al , ; Marrone et al , , ). In agreement with these works, we found that compounds known to induce autophagy, notably promethazine, are able to bypass the reduced expression of C9ORF72 and can promote the clearance of DPR proteins, thus reducing their toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Promethazine is a sedative and antihistamine drug with antipsychotic effects that belongs to a class of phenothiazine derivatives known to activate autophagy in neuronal cell cultures (Tsvetkov et al , ). Interestingly, these compounds ameliorate neuronal cell dysfunctions and prevent neuronal cell death in SOD1, TDP‐43, and FUS cellular and animal models of ALS (Barmada et al , ; Patten et al , ; Marrone et al , , ). Furthermore, pimozide, a phenothiazine derivative related to promethazine, displayed some promising effects in a short randomized clinical trial of sporadic ALS (Patten et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Human iPS cells lines, derived from three different donors, expressing FUS with a C-terminal GFP fluorescent marker were used. All were generated using CRISPR/Cas9 assisted tagging and mutagenesis and have been previously described 46,68 . In summary: JS-SL-C1 iPS cells expressing either wild-type or P525L FUS GFP 68 were previously generated from a healthy female donor 69 .…”
Section: Methodsmentioning
confidence: 99%